Voltage-gated sodium channels gene expression in Burning Mouth Syndrome: a case-control study - Carina DOMANESCHI; Vanessa Juliana Gomes CARVALHO; Bruno Munhoz MAROTTA; Norberto Nobuo SUGAYA; Fábio Daumas NUNES; Camila de Barros GALLO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Burning mouth syndrome (BMS) is a condition characterized by painful symptoms of the oral mucosa, despite the absence of any clinical signs. Its etiology is unknown, and there is still no effective treatment to date. Current evidence has shown neuropathic impairment in BMS patients. Neuropathic pain can be related to the dysfunction of voltage-gated sodium channels, considering that these receptors regulate the induction of action potentials in nociceptive neurons. This study evaluated the gene expression of voltage-gated sodium channels Na v 1.7, Na v 1.8 and Na v 1.9 in these patients. The gene expressions of these channels were assessed by real time RT-PCR analysis of fresh-frozen tongue biopsies in a case-control study composed of 12 patients with BMS, and 5 healthy control patients, proportionally matched by sex and age, and analyzed using the 2^(-Delta Delta CT) method. There was no statistically significant difference between the analyzed groups, despite the increase in Na v 1.7 (fold-change = 3.13, p = 0.52) and decrease in Na v 1.9 (fold-change = 0.45, p = 0.36) gene expression in the BMS group. The Na v 1.8 gene was not expressed in any of the samples analyzed. Although the gene expression in the voltage-gated sodium channels in BMS under study seems to be comparable with that of the normal oral mucosa, the functionality of these channels in BMS has not yet been identified, thus suggesting that further research is needed to better understand these voltage-gated sodium channels.